REDUCING SUGARS CONTENT AND CHIPPING QUALITY OF TUBERS OF POTATO CULTIVARS AFTER STORAGE AND RECONDITIONING - Singh, Brajesh; Ezekiel, R.; Kumar, Dinesh; Kumar, Suresh (Potato Journal, 2013)
Dry matter and reducing sugars content were determined in 11 potato cultivars grown at four locations after 100 and 210 days of storage (DOS) at 4, 8, 12, 16 and 20oC. [After 210 DOS, the dry matter content was higher in tubers stored at 12 and 16oC depending on the location]. After 100 DOS, the reducing sugars content was higher in tubers stored at 4 and 8oC resulting in dark and unacceptable chip colour. When stored at 12, 16 and 20oC, the reducing sugars content decreased significantly after 100 DOS but the chip colour was acceptable only in Kufri Chipsona-1 and Kufri Chipsona-2, and in Kufri Jyoti grown at Patna. Reconditioning at 20oC resulted in significant decrease in reducing sugars content and improvement in chip colour but it was still unacceptable. Increasing the reconditioning period from 3 to 6 weeks did not improve the chip colour. Cultivars differed significantly in their response to reconditioning and it was effective only in few cultivars stored at different temperatures. After 210 DOS, the reducing sugars content increased and chip colour deteriorated in all the cultivars.